2018
DOI: 10.1007/s12011-018-1511-y
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Absorption and Renal Excretion of Fluoride After Ingestion of a High-Fluoride Dentifrice

Abstract: This study aimed to evaluate the gastrointestinal absorption and renal excretion of fluoride after the ingestion of high-fluoride dentifrice. Twelve volunteers participated in this in vivo, crossover, and blinded study. In three experimental phases, the volunteers were randomly assigned to one of three treatment groups, who ingested either the following: distilled and deionized water (control), conventional dentifrice (1100 μg/g), or high-fluoride dentifrice (5000 μg/g). Both dentifrices contained fluoride in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…From our initial selection of 1,273 articles, 46 met the inclusion criteria and only 28 were included in our systematic review as digital data concerning the estimation of daily F intake was reported by authors (Figure 1). Among these 46 articles, 18 were used only for the discussion and were not included into our database since they reported urine F excretion without any estimation of the TDFI [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Concerning the 28 selected studies, they were carried out in countries all over the world with almost half of the studies (43%) carried out in Brazil (Supplementary Figure 1) .…”
Section: Resultsmentioning
confidence: 99%
“…From our initial selection of 1,273 articles, 46 met the inclusion criteria and only 28 were included in our systematic review as digital data concerning the estimation of daily F intake was reported by authors (Figure 1). Among these 46 articles, 18 were used only for the discussion and were not included into our database since they reported urine F excretion without any estimation of the TDFI [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Concerning the 28 selected studies, they were carried out in countries all over the world with almost half of the studies (43%) carried out in Brazil (Supplementary Figure 1) .…”
Section: Resultsmentioning
confidence: 99%
“…6,13 The indications and benefits of high-F dentifrices for patients at high risk of caries are well described in the literature, as they maintain high and constant levels of salivary fluoride compared with conventional dentifrices. 3,10,23,24 These data were corroborated by the present study, in which it was observed that the three dentifrices analysed provided an increase in the availability of F after brushing. However, the F values observed in the saliva for the high-fluoride dentifrices were higher compared with the conventional dentifrice 2 h after brushing.…”
Section: Discussionmentioning
confidence: 99%